Improvement of the chemotherapy and pharmaceutical service management system by monitoring drug prescription errors in oncology patients - Zalyhina, Ye.V.; Bereznytskyi , Ya.S. (Medicni Perspektivi, 2025)
In hospital conditions the prevalence of errors in prescribing drugs is 2-94%. The prevalence of errors in prescribing chemotherapeutic drugs is 1-3% of adults. An important area of improvement of the chemotherapy and pharmaceutical service management system is the introduction of innovative technologies aimed at automating quality control processes. The purpose of the work is to compare the level of errors while using drugs in oncology patients and patients of the surgical department and to form principles for improving the management system of chemotherapy and pharmaceutical services by automating processes. During the research, an analysis of scientific publications and a retrospective analysis (examination of internal documents) were carried out, followed by generalization and comparison of data. Statistical processing of the results was carried out using the method of interval dynamic series analysis. Error rates were presented using median and quartiles (Me [Q1; Q3]), comparisons were made using the Mann-Whitney test (p<0.05). The level of errors in appointment lists in the surgical hospital for the analyzed period was 27.2 [19.3; 45.9], at the same time in the oncology department this indicator was 249.2 [220.8; 390.6]. That is, the rate of errors in the oncology department is on average 8.9 (5.6-18.3) times higher (p<0.001) than in the surgical hospital. The level of errors in appointment lists in the oncology department significantly (p<0.05) decreased from 379.17 in the first half of the analyzed period (03.01.23-09.30.23) to 212.67 in the next similar period (10.01.23-04.01.24), which is explained by the introduction of an automated decision-making algorithm in the information system. Therefore, it can be concluded that the level of errors in the appointment lists in the oncology department is on average by 8.9 (5.6-18.3) times higher (p<0.001) than in the surgical hospital, as well as the level of errors in the appointment lists of the oncology department significantly (p<0.05) decreased from 379.17 to 212.67 in the first half of the analyzed period in the next similar period due to timely detection and analysis of deviations, implementation of an automated decision-making algorithm in the information system of the medical center, improvement of individual work with by health care specialists and revision of professional roles, as well as to change the structure of providing medical care.